Aktivitas Fitoestrogen Senyawa Alkaloid dari Bunga Telang (Clitoria ternatea) Menggunakan Analisis In Silico - Ramadani, Sofi Ramadani (Maliki Interdisciplinary Journal, 2024)
The decrease in estrogen levels during menopause can lead to health issues, and exogenous estrogen hormone therapy is often used despite increasing the risk of tumors. Phytoestrogens, which are safer plant compounds, present an alternative, one of which comes from the alkaloids of the Butterfly Pea flower (Clitoria ternatea). This study examines the potential of phytoestrogens from these alkaloids through pharmacokinetic analysis, structural similarity, and molecular docking. The results indicate that Cephalotaxinone stands out due to its significant structural similarity and binding affinity to Estrogen Receptor Alpha, as well as having a good pharmacological profile. Thus, Cephalotaxinone has the potential as a safe alternative phytoestrogen for therapies related to decreased estrogen, but further studies are needed.